2014
DOI: 10.1021/jp508270g
|View full text |Cite
|
Sign up to set email alerts
|

Strength of the Pnicogen Bond in Complexes Involving Group Va Elements N, P, and As

Abstract: A set of 36 pnicogen homo- and heterodimers, R3E···ER3 and R3E···E′R′3, involving differently substituted group Va elements E = N, P, and As has been investigated at the ωB97X-D/aug-cc-pVTZ level of theory to determine the strength of the pnicogen bond with the help of the local E···E′ stretching force constants k(a). The latter are directly related to the amount of charge transferred from an E donor lone pair orbital to an E′ acceptor σ* orbital, in the sense of a through-space anomeric effect. This leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
102
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(107 citation statements)
references
References 143 publications
3
102
2
Order By: Relevance
“…Often the argument is passed forward that the BDE values might describe at least qualitatively the correct trend of the intrinsic bond strength. However, numerous examples have been shown [35,[37][38][39]46,96] that this hope lacks any quantum mechanical basis and therefore it is always desirable to obtain the intrinsic strength of a bond from vibrational spectroscopy as the local stretching force constants can be always derived.…”
Section: The Danger Of Using Bde Values As Intrinsic Bond Strength Dementioning
confidence: 99%
See 1 more Smart Citation
“…Often the argument is passed forward that the BDE values might describe at least qualitatively the correct trend of the intrinsic bond strength. However, numerous examples have been shown [35,[37][38][39]46,96] that this hope lacks any quantum mechanical basis and therefore it is always desirable to obtain the intrinsic strength of a bond from vibrational spectroscopy as the local stretching force constants can be always derived.…”
Section: The Danger Of Using Bde Values As Intrinsic Bond Strength Dementioning
confidence: 99%
“…The preferred tool in this work will be a dynamical model of the bond strength based on vibrational spectroscopy and the theory of local modes, which was introduced by Konkoli and Cremer [28] and which, since then, has been proved to be physically sound, generally applicable, and a direct way of determining the intrinsic strength of a bond. [29][30][31] The usefulness of the local vibrational mode description of the bond strength has been documented by the characterization of CC bonds, [29,[32][33][34] NN bonds, [35] CO bonds, [36] CX bonds with X 5 F, Cl, Br, I, [37][38][39][40] H-bonding, [41][42][43][44] pnicogen bonding, [45,46] and the characterization of isotopomers. [47] The main objectives of this work are (i) to critically reevaluate previously published reverse BLBS relationships, (ii) to introduce reliable bond strength orders (BSOs) needed for characterizing unusual bonds, (iii) to elucidate the interplay of electronic and electrostatic factors determining the stability of electron-rich bonds, and (iv) to derive a rational for any deviation from the commonly known inverse BLBS relationships.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the local stretching force constant k a is a superior bond strength measure compared to the often used bond dissociation energies (BDE) and bond dissociation enthalpies (BDH) as they contain cumulative effects of geometry relaxation, multiple bonding interactions, and also electronic density reorganizations of the dissociated fragments . Local stretching force constants k a have been successfully used to determine the intrinsic bond strength of covalent bonds such as: CC bonds, NN bonds, NF bonds, CO bonds, and CX (X=F, Cl, Br, I) bonds, and weak chemical interactions such as: hydrogen bonding, halogen bonding, pnicogen bonding, chalcogen bonding, tetrel bonding, and recently BH···π interactions …”
Section: Introductionmentioning
confidence: 99%
“…9,10,11,12,13,14 Over the past few years other non-conventional noncovalent interactions have gained attention, such as tetrel bonding, 15,16,17,18,19 pnictogen bonding, 20,21,22,23,24,25,26,27,28,29,30,31 chalcogenide bonding, 32,33,34,35,36,37,38,39,40,41,42,43,44 and even aerogen bonding. 45 All follow the same bonding scheme, namely a -hole, 46 which can be viewed comparably to hydrogen bonding: X-D … A, where X is any atom, D is the donor atom and A is the acceptor atom.…”
Section: Introductionmentioning
confidence: 99%